Two new species and new records of Liocanthydrus Guignot (Coleoptera, Noteridae) from Brazil - Guimarães, Bruno Aguilar Carrilho; Ferreira-Jr, Nelson (Zootaxa, 2015)
Two new species of Liocanthydrus Guignot, L. zanclus sp. nov. and L. mecespilus sp. nov., are described and illustrated from the Brazilian states of Goiás and Espírito Santo, Minas Gerais and Rio de Janeiro, respectively. New records from Brazil are also provided: Liocanthydrus clayae (J. Balfour-Browne) from the state of Pará, L. bicolor (J. Balfour-Browne) from the states of Amazonas and Pará and L. uniformis (Zimmermann) from the states of Espírito Santo, Maranhão and Pará. The previous key of Liocanthydrus is modified to include the new species.